Édito - Questionner les milieux éducatifs par les dispositifs et l'activité - Mariagrazia Cairo Crocco; Christine Félix; Frédéric Saussez (Recherches en Éducation)
Over the past thirty years, a profound transformation of public action and educational policies has begun : competitiveness and performance indicators have taken on a greater role in an educational ecosystem that is now organised and managed by mechanisms. In this thematic dossier, we are particularly interested in this structuring by devices in order to analyse the transformations of power relations, prescriptions, norms and frameworks of the work of education professionals, as well as the way in which these transformations contribute to shaping new professionalities. The aim is to explore the processes and mechanisms by which a system can affect, in the sense of transforming, the activity of the professionals concerned and the beneficiaries involved in it. The proposed analyses concern the field of teaching, education, training and vocational guidance in the French, Swiss and Quebec regions.